Performance Analysis of the Accounting Information System on the Regional Owned Enterprise (BUMD) Tirta Medal Sumedang - Adinegara, Ahmad Andy; Nurfajar, Reja; Cahyani, Cahyani; Nurazizah, Imas Yuni (Journal of Business, Accounting and Finance, 2025)
This study examines the performance of accounting information systems at BUMD Tirta Medal Sumedang. The research method used is qualitative-descriptive, with a focus on the collection of primary data through interviews and secondary data via literature reviews. The results of the research showed that the performance of the accounting information system at BUMD Tirta Medal Sumedang is already optimal; the information system of Situntas Accounting is considered to have met the needs based on the characteristics of the company; it is easy to understand and operate; and the quality of the financial information generated is timely, relevant, and accurate. The results of this research provide recommendations for the development of cash flow report features with direct methods, synchronization of recording of customer payments paid through bank transfer system on accounting system, digitization of records on fixed asset details and spread details of branch network BUMD Tirta Medal Sumedang, integration with other information systems such as the information system of the planning part, human resources information system, and customer service information system. The implementation of these measures is expected to improve the performance of accounting information systems as well as provide more accurate, relevant, and timely financial information to BUMD Tirta Medal Sumedang.